A Great Media Wall - China's Film Policy and Its Impacts on U.S. Film Exporters. Issue 1 (1st March 2007) - Lin, Mu
This paper attempts to explore issues about China's film industry that are of interest to Hollywood majors, or foreign investors in general, i.e., the regulatory framework of China's film policies regarding foreign investment, the impact of such policies on foreign film investors, and the long-term policy change in this regard. This study is based on an extensive examination of China's filmrelated legal documents, press reports on foreign media investments in China, and academic literature related to the subject.